Kajian ketebalan dan lama pengeringan terhadap sifat kimia, sensoris dan fisik opak tepung ubi kayu (Manihot esculenta C) - Nurdjanah, Siti; Putri, Aulia; Susilawati, Susilawati; Nurbaiti, Nurbaiti; Larassati, Dyah Putri (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Opak is a traditional food from Indonesia made from fresh cassava. But fresh cassava has short shelf life because of the undergoing post-harvesting physiological deterioration shortly after harvest. Therefore, this research tried to replace the fresh cassava with cassava flour as a raw material for opak production. The purpose of this study are to determine the thickness and drying time in the production of opak from cassava flour which produces the best sensory, physical and chemical properties. Opak was made with thickens variations of (K1) 0.5 mm, (K2) 1 mm, (K3) 1.5 mm, and (K4) 2 mm with drying time variations of (P1) 1 hour, (P2) 2 hours, and (P3) 3 hours. The results show that there has interaction effect between thickness and drying time toward the best opak cassava flour, namely 1 mm thickness with 3 hours drying time with color characteristics 1.40 (brownish yellow), texture 4.02 (crispy), flavour 3.2 (slightly typical of cassava), the bulk density was 0.59 g/mL, the water absorption capacity was 5.49 %, and the oil absorption capacity was 0.03 g/g, the moisture is 0.20 %, the ash content is 2.89 %, the protein content is 1.26, fat content 27.12 %, and 68.51 % of carbohydrates.